Soft Skill Development for Ecosystem Services Measurement to Support FMUs and Aceh Community Forest Management - Ulfa Hansri Ar Rasyid; Ashabul Anhar; Subhan Subhan; Ali M. Muslih; Anna Farida; Lola Adres Yanti; Tuti Arlita; Arif Habibal Umam (Magister of Forestry,Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Utilization of data and information on ecosystem services is used as a reference in the management of natural resources and the environment as well as a guide for policy makers to determine priority locations in critical ecosystem restoration. There are challenges for Forest Management Unit (FMU) staff and community members to accurately collect and report specific information on forest carbon, biodiversity, supply forest types, and cultural ecosystem services. This service aims to facilitate FMU staff and members of the social forestry community in Aceh Province to receive Excel-based training on ecosystem services tools. The method used is counseling through training activities carried out for six days using excel-based ecosystem services tools, namely forest carbon, tree biodiversity, and forest integrity Assessment (FIA). The participants of this activity were 22 participants who came from KPH staff, forest community groups, local government agencies (BKSDA Aceh, BPDASL KA, TNGL), as well as staff and students of Forestry at Syiah Kuala University. The results obtained from this activity are direct understanding and practice by participants regarding the use of excel-based ecosystem service tools.